2016
DOI: 10.3389/fmicb.2016.00754
|View full text |Cite
|
Sign up to set email alerts
|

New Reassortant H5N6 Highly Pathogenic Avian Influenza Viruses in Southern China, 2014

Abstract: New reassortant H5N6 highly pathogenic avian influenza viruses (AIVs) were isolated from apparently healthy domestic ducks in Southern China in 2014. Our results show that the viruses grew efficiently in eggs and replicated systemically in chickens. They were completely lethal in chicken (100% mortality), and the mean death time was 6 to 7 days post-inoculation. The viruses could transmit in chickens by naïve contact. BLAST analysis revealed that their HA gene was most closely related to A/wild duck/Shangdong/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
14
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 14 publications
2
14
0
Order By: Relevance
“…It is important to understand the origins and genesis of these subtype viruses and to determine their relationships with other subtype viruses in this clade. Previous studies revealed that the HPAI H5N6 virus contained the hemagglutinin (HA) gene of H5 clade 2.3.4.4, the internal genes of H5 clade 2.3.2.1, and the NA gene from the H6N6 avian virus (9,12,13). Based on the genetic evidence, HPAI H5N6 virus likely originated from migratory waterfowl (14).…”
mentioning
confidence: 99%
“…It is important to understand the origins and genesis of these subtype viruses and to determine their relationships with other subtype viruses in this clade. Previous studies revealed that the HPAI H5N6 virus contained the hemagglutinin (HA) gene of H5 clade 2.3.4.4, the internal genes of H5 clade 2.3.2.1, and the NA gene from the H6N6 avian virus (9,12,13). Based on the genetic evidence, HPAI H5N6 virus likely originated from migratory waterfowl (14).…”
mentioning
confidence: 99%
“…However, virus isolation from apparently healthy ducks and geese in live bird markets in China was also described (Jiao et al, 2016;Sun et al, 2016). Increased mortality in galliforms as well as increased mortality and neurological signs (torticollis, ataxia) in domestic ducks were reported from the Republic of Korea (OIE reports).…”
Section: Phenotypic Characterisationmentioning
confidence: 99%
“…Increased mortality in galliforms as well as increased mortality and neurological signs (torticollis, ataxia) in domestic ducks were reported from the Republic of Korea (OIE reports). However, virus isolation from apparently healthy ducks and geese in live bird markets in China was also described (Jiao et al, 2016;Sun et al, 2016). A Korean A(H5N6) isolate was tested in 6-week-old SPF chickens inoculated intravenously and the IVPI value was 2.66 .…”
Section: Phenotypic Characterisationmentioning
confidence: 99%
See 1 more Smart Citation
“…So far human cases have been constrained to South-East and Eastern Asia but concerns remain about the potential for a virulent human pandemic due to continued mutation of these viruses. 54 All these new pathogens draw attention to the fact that we are a global community and problems in one country can quickly become problems worldwide. Continual erosion of natural habitats and increasing numbers of humans living in closer proximity to zoonotic hosts make further epidemics of novel viruses inevitable and given how quickly they can spread with modern global transport.…”
Section: The Non-global Nature Of Healthcareassociated Pneumoniamentioning
confidence: 99%